Real-time motion capture in autodesk 3Ds max using microsoft kinect - Panekat, Mithun (2012)
The concept of motion capture is used in many industries such as the film and gaming industry. It involves recording the actions of human actors and mapping this motion to 2D and 3D models in a virtual world, such that the models perform the exact same motion. The main objective of this project is to explore and implement real time motion capturing in Autodesk 3DS Max using Microsoft Kinect.